A Framework for Evaluating Cost Control Procedures for a Process. - Stallman, James C. (The Accounting Review, 1972)
Abstract The article reports that the evaluation of the cost control procedures applied to a process is facilitated by viewing the control objective as minimizing a whole set of costs including the efficiency cost incurred in the operation of the process and all of the control procedure costs. Thus, proposed changes in control procedures can be evaluated by determining their net effect on the total of this set of costs. Two approaches to controlling efficiency cost were discussed along with some indication of the types of procedures required by each. The first approach, that of preventive controls, has its primary effect on efficiency cost through the frequency of occurrence of operating problems. The second approach, that of detection-correction controls, has its effect on efficiency cost by influencing the length of time operating problems are allowed to exist in the process. It can be argued that budget performance reporting, a major contribution of the accountant to process cost control, serves both control approaches.